Safety and security of radiation sources in the aftermath of 11 September 2001 - Lubenau, Joel O; Strom, Daniel J (Health physics (1958), 2002)
The attack on the United States on 11 September 2001 resulted in an increased awareness of the need for safety and security measures to protect against terrorism. The potential use of radiation sources in terrorism, in particular radioactive sources, was recognized prior to 11 September 2001, but has taken on new significance since. The planning of security measures for radioactive sources must take greater account of the potential for deliberate acts to attack or use radioactive sources to expose people and cause contamination. The potential consequences of an act of terrorism using radioactive sources can be gauged from the consequences of serious accidents that have occurred involving radioactive sources. These include fatal and injurious radiation exposures, contamination of the environment, and serious economic and psychosocial costs the total effect of which is mass disruption. Steps are being taken to improve security for radioactive sources but strategic approaches that can minimize the threat of radiological terrorism should be considered. When justifying a practice that uses radioactive sources, the potential for diversion or use in terrorism should be considered to be a detriment. In this regard, the consideration and development of alternatives to radioactive sources, such as radiation producing machines, have been recommended by terrorism experts as measures to reduce the threat of radiological terrorism. If a practice using radioactive sources is determined to be justified, the need for special security measures to protect against terrorism should then become part of the safety assessment.